Extending the Aerolysin Family: From Bacteria to Vertebrates - Szczesny, Pawel (Public Library of Science, 2011)
A number of bacterial virulence factors have been observed to adopt structures similar to that of aerolysin, the principal toxin of Aeromonas species. However, a comprehensive description of architecture and structure of the aerolysin-like superfamily has not been determined. In this study, we define a more compact aerolysin-like domain – or aerolysin fold – and show that this domain is far more widely spread than anticipated since it can be found throughout kingdoms. The aerolysin-fold could be found in very diverse domain and functional contexts, although a toxic function could often be assigned. Due to this diversity, the borders of the superfamily could not be set on a sequence level. As a border-defining member, we therefore chose pXO2-60 – a protein from the pathogenic pXO2 plasmid of Bacillus anthracis. This fascinating protein, which harbors a unique ubiquitin-like fold domain at the C-terminus of the aerolysin-domain, nicely illustrates the diversity of the superfamily. Its putative role in the virulence of B. anthracis and its three dimensional model are discussed.